Is short term debt maturity linked to real earning management? - Liem Nguyen Thanh; Trung Trinh Quoc; Khuong Nguyen Vinh; Thuy Cao Thi Mien (Management, 2022)
This paper explores the association between the maturity of short-term debt and real earnings management in the context of an emerging market. We use a panel dataset of listed firms in Vietnam over the period from 2009 to 2017 and employ conventional methods for panel data analysis. Our work contributes by documenting a non-linear relationship between short-term debt maturity and manipulation of earnings. In particular, businesses prefer to refrain from manipulating earnings at low short-term debt maturity levels but are likely to manage them at higher short-term debt maturity levels. Under a battery of robustness evaluations, this result remains unchanged. This means that investors/lenders of firms should be vigilant with the information recorded on financial statements because managers can manage corporate earnings, especially at high short-term debt levels.